CO2-Philic [EMIM][Tf2N] modified silica in mixed matrix membrane for high performance CO2/CH4 separation - Siti Nur Alwani, Shafie; Wen, Xuan Liew; Nik Abdul Hadi, Md Nordin; Bilad, Muhammad Roil; Norazlianie, Sazali; Zulfan, Adi Putra; Mohd Dzul Hakim, Wirzal (Wiley, 2019)
Separation of carbon dioxide (CO 2 ) from methane (CH 4 ) using polymeric membranes is limited by trade-off between permeability and selectivity as depicted in Robeson curve. To overcome this challenge, this study develops membranes by incorporating silica particles (Si) modified with [EMIM][Tf 2 N] ionic liquid (IL) at different IL:Si ratio to achieve desirable membrane properties and gas separation performance. Results show that the IL:Si particle has been successfully prepared, indicated by the presence of fluorine and nitrogen elements, as observed via Fourier-Transform Infrared Spectroscopy (FTIR) and X-ray Photoelectron Spectrometer (XPS). Incorporation of the modified particles into membrane has given prominent effects on morphology and polymer chain flexibility. The mixed matrix membrane (MMM) cross-section morphology turns rougher in the presence of IL:Si during fracture due to higher loadings of silica particles and IL. Furthermore, the MMM becomes more flexible with IL presence due to IL-induced plasticization, independent of IL:Si ratio. The MMM with low IL content possesses CO 2 permeance of 34.60 ± 0.26 GPU with CO 2 /CH 4 selectivity of 85.10, which is far superior to a pure polycarbonate (PC) and PC-Sil membranes at 2 bar, which surpasses the Robeson Upper Bound. This higher CO 2 selectivity is due to the presences of CO 2 -philic IL within the MMM system.